Software agents meet internet of things. Issue 3 (4th January 2018) - Maamar, Zakaria; Faci, Noura; Kallel, Slim; Sellami, Mohamed; Ugljanin, Emir
Abstract : The last few years have seen a rapid democratization of things to the extent that they have become omnipresent in our surroundings and daily lives. Many buzzwords like smart cities, smart homes, and smart wrists exemplify thing democratization. Unfortunately, Internet of Things (IoT) adoption is slowing down due to first, the nature of things being usually "passive" and second, the multiplicity of things' development tools and communication standards. Both are impacting the quality of IoT applications and undermining the capabilities that these applications could offer to users. In this position paper, we discuss the "agentification" of things, using norms and commitments, as a means to address their passive nature. At the conceptual level, norms ensure that things operate in accordance to users' best interests. Also, at the operational level, commitments ensure that things will not deviate from the prescribed norms and hence, avoid violations that could lead to penalties. An architecture supporting thing agentification along with some ongoing efforts are discussed in this paper.